Application of token economy to increase learning concentration for children with Autism Spectrum Disorder (ASD) - Ainayya Salsabili Aulia,; Ni'matuzahroh,; Diah Karmiyati, (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The token economy is a behavior modification technique that can be used to increase desired behavior or reduce undesirable behavior in individuals, including children with Autism Spectrum Disorder (ASD). This research aims to determine the effectiveness of implementing a token economy to increase learning concentration in children with ASD. The method used in this research is quasi-experimental with a single-case experimental design described in the ABAB model. The subject in this study was a child with ASD who had problems with the ability to concentrate during learning. The instrument used in this research is a behavior checklist sheet for aspects of learning concentration adapted to the characteristics of children with ASD subjects. This research uses data presentation and data analysis techniques in the form of descriptive graphs, which show that applying the token economy is practical in increasing the learning concentration of children with ASD. The token economy is proven by increased learning concentration scores during the research phase, which consists of four measurement aspects: the focus defense aspect, the task completion aspect, the perseverance aspect, and the regularity aspect.